Portuguese Language Version of the Tampa Scale for Kinesiophobia [13 Items]. Issue 1 (March 2013) - Cordeiro, Nuno; Pezarat-Correia, Pedro; Gil, João; Cabri, Jan
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to translate and adapt the Tampa Scale for Kinesiophobia to the Portuguese language and culture [TSK-PT], and validate its use in Portuguese patients with chronic low back pain [CLBP]. Methods The procedures were performed following published international guidelines. Patients with CLBP were recruited to complete the TSK-PT and visual analog scales [VAS] for pain and for confidence in low back movement. A portion of the same patients also completed a second TSK-PT questionnaire after a seven-day interval to establish test-retest reliability. After three months, all of the original patients completed the questionnaire again to assess its responsiveness using standardized effect size and standardized response mean. Results At baseline, 166 patients with chronic LBP completed the series of questionnaire instruments. After an interval of seven days, forty one patients again completed the series of instruments. Three months after baseline, all 166 patients again completed the questionnaire series. The Cronbach alpha of 0.82 indicated good internal consistency of the TSK-PT total score, and the one-week intraclass correlation coefficient of 0.99 indicated exceptional test-retest reliability. A three-factor solution could be found on factorial analysis. There were significant correlations between the TSK-PT total score and both VAS Pain and VAS Confidence scores. The standardized effect size of the TSK-PT was 0.50 and the standardized response mean was 0.67. Conclusions The TSK-PT has proven to be a valid and reliable tool in the assessment of kinesiophobia in patients with CLBP.